Minimally invasive surgical staging for early stage ovarian cancer: A long-term follow up. Issue 7 (July 2021) - Gallotta, Valerio; Jeong, Soo Young; Conte, Carmine; Trozzi, Rita; Cappuccio, Serena; Moroni, Rossana; Ferrandina, Gabriella; Scambia, Giovanni; Kim, Tae-Joong; Fagotti, Anna
Abstract: Introduction: The standard treatment for epithelial early stage ovarian cancer (eEOC) includes laparotomic surgical staging, according to ESGO-ESMO guidelines. In the last decade, many investigators have assessed the safety and feasibility of minimally invasive surgery (MIS) staging in properly selected patients. However, survival data related to different surgical approaches (open versus MIS) are extremely limited. The aim of this study is to analyze the long-term oncological outcomes in eEOC patients treated with MIS. Materials and methods: This is a multicenter observational retrospective study conducted in two tertiary oncological centers. We selected all consecutive women who underwent a laparoscopic or robotic staging for eEOC. Results: From January 2008 to December 2016, 254 eEOC patients underwent a MIS staging (188 laparoscopic staging and 66 robotic staging). Overall, 18.1% of patients were upstaged due to pathological findings. A total of 203 (79.9%) patients received platinum-based adjuvant chemotherapy. After a median follow-up of 61 months (range 13–118), 39 (15.3%) patients experienced recurrence. The 5-years progression free survival (PFS) and overall survival rates were 84.0% and 93.8%, respectively. In the univariate analysis, favorable variables influencing PFS were young age (≤45 years), non-serous histotype, tumor grade 1-2, and FIGO stage IA/IB. In the multivariate analysis, only grade 3 was shown to keep its negative independent prognostic value (HR = 3.47; p = 0.004), whereas FIGO stage ≥ IC showed a trend toward significance (HR = 1.75; p = 0.099). Conclusion: This retrospective study represents the longest follow-up of eEOC patients managed by MIS. The MIS is a valuable therapeutic option in appropriately selected patients, although a randomized controlled trial is needed.